SUPERVISI KEPALA MADRASAH DALAM PENGEMBANGAN PROGRAM MATA PELAJARAN - Zakiyaman, Muhammad (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Output or a graduate of a school is said to be good if students excel. And student learning outcomes or achievements of the students is a reflection of the performance of teachers. It is described in the research results Goodblad (1976) that teachers have a significant role for every success in the learning process. The study was later published under the title Behind the Classroom doors explaining that when teachers have entered the classroom and closed the door - the door of the classroom, the learning quality is determined more by the teacher. The description contains the purpose that the quality of learning that is the result of a very influential teacher performance on student achievement. While the teacher is good or not the performance is determined by the principal. due to poor educational institution, including teaching staff (teachers) depends on the boss, he is the person most responsible for the success of the school. Teachers performance in carrying out the task of learning at the school is influenced by external and internal factors. External factors including headmaster leadership, organizational climate, and organizational culture.